A Pyridazine-Based Fluorescent Probe Targeting Aβ Plaques in Alzheimer's Disease. (27th February 2018) - Park, Yong Dae; Kim, Jeum-Jong; Lee, Sungbeom; Park, Chul-Hong; Bai, Hyoung-Woo; Lee, Seung Sik
Abstract : Accumulation of β -amyloid (A β ) plaques comprising A β 40 and A β 42 in the brain is the most significant factor in the pathogenesis of Alzheimer's disease (AD). Thus, the detection of A β plaques has increasingly attracted interest in the context of AD diagnosis. In the present study, a fluorescent pyridazine-based dye that can detect and image A β plaques was designed and synthesized, and its optical properties in the presence of A β aggregates were evaluated. An approximately 34-fold increase in emission intensity was exhibited by the fluorescent probe after binding with A β aggregates, for which it showed high affinity ( K D = 0.35 µ M). Moreover, the reasonable hydrophobic properties of the probe (log P = 2.94) allow it to penetrate the blood brain barrier (BBB). In addition, the pyridazine-based probe was used in the histological costaining of transgenic mouse (APP/PS1) brain sections to validate the selective binding of the probe to A β plaques. The results suggest that the pyridazine-based compound has the potential to serve as a fluorescent probe for the diagnosis of AD.